Evidence of streptococcal origin of acute non-necrotising cellulitis: a serological study - Karppelin, M.; Siljander, T.; Haapala, A.-M.; Aittoniemi, J.; Huttunen, R.; Kere, J.; Vuopio, J.; Syrjänen, J. (European journal of clinical microbiology & infectious diseases, 2015)
Bacteriological diagnosis is rarely achieved in acute cellulitis. Beta-haemolytic streptococci and Staphylococcus aureus are considered the main pathogens. The role of the latter is, however, unclear in cases of non-suppurative cellulitis. We conducted a serological study to investigate the bacterial aetiology of acute non-necrotising cellulitis. Anti-streptolysin O (ASO), anti-deoxyribonuclease B (ADN) and anti-staphylolysin (ASTA) titres were measured from acute and convalescent phase sera of 77 patients hospitalised because of acute bacterial non-necrotising cellulitis and from the serum samples of 89 control subjects matched for age and sex. Antibiotic treatment decisions were also reviewed. Streptococcal serology was positive in 53 (69 %) of the 77 cases. Furthermore, ten cases without serological evidence of streptococcal infection were successfully treated with penicillin. Positive ASO and ADN titres were detected in ten (11 %) and three (3 %) of the 89 controls, respectively, and ASTA was elevated in three patients and 11 controls. Our findings suggest that acute non-necrotising cellulitis without pus formation is mostly of streptococcal origin and that penicillin can be used as the first-line therapy for most patients.